Spectrum of PALB2 germline mutations and characteristics of PALB2‐related breast cancer: Screening of 16, 501 unselected patients with breast cancer and 5890 controls by next‐generation sequencing. Issue 14 (27th April 2020) - Zhou, Jiaojiao; Wang, Honglian; Fu, Fangmeng; Li, Zhanwen; Feng, Qingjian; Wu, Weizhu; Liu, Yun; Wang, Chuan; Chen, Yiding
Abstract : Background: Partner and localizer BRCA2 ( PALB2 ) is a breast cancer predisposition gene, but the clinical relevance of PALB2 germline mutations in Chinese patients with breast cancer remains unknown. This study attempted to investigate the full prevalence and spectrum of PALB2 germline mutations in China and the associations between PALB2 germline mutations and breast cancer risk. Methods: A total of 21, 216 unselected patients with breast cancer were enrolled from 10 provinces in China, and 5890 Chinese women without cancer were enrolled as healthy controls. PALB2 screening was based on next‐generation sequencing. Results: A total of 16, 501 BRCA1/2 ‐negative patients with breast cancer were analyzed. Deleterious PALB2 mutation carriers accounted for 0.97% (n = 160) in the breast cancer cohort and for 0.19% (n = 11) in the healthy control cohort. Forty‐one novel PALB2 germline mutations were identified. A high frequency of PALB2 c.751C>T was detected, and it accounted for 10.63% of the PALB2 germline mutations detected (17 of 160). PALB2 mutations were significantly associated with increased breast cancer risk (odds ratio [OR], 5.23; 95% confidence interval [CI], 2.84‐9.65; P < .0001), especially among women 30 years old or younger (OR, 10.09; 95% CI, 3.95‐25.79; P < .0001). Clinical characteristics, including a family history, bigger tumor size, triple‐negative breast cancer, positive lymph nodes, and bilateral breast cancer, were closely related to PALB2 mutations. Conclusions: This study revealed a comprehensive spectrum of PALB2 germline mutations and characteristics of PALB2 ‐related breast cancer in China. PALB2 germline mutations confer a moderately increased risk for breast cancer but profoundly increase breast cancer risk for those 30 years old or younger in the Chinese population. Abstract : This study reveals a comprehensive spectrum of PALB2 germline mutations and characteristics of PALB2 ‐related breast cancer, including the PALB2 ‐related breast cancer risk and distinctive clinical characteristics. Clinically, this study will provide solid evidence for the genetic counseling of patients with breast cancer and healthy women with PALB2 germline mutations, especially in the Chinese population and among those with Chinese ethnicities worldwide.